2021
DOI: 10.3389/fphar.2021.615104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Combined With Microbubbles Loading BDNF Retrovirus to Open Blood–Brain Barrier for Treatment of Alzheimer’s Disease

Abstract: Background: Brain-derived nerve growth factor (BDNF) is a promising effective target for the treatment of Alzheimer’s disease (AD). BDNF, which has a high molecular weight, has difficulty in crossing the blood–brain barrier (BBB). The study aimed to prepare microbubbles loading brain-derived nerve growth factor (BDNF) retrovirus (MpLXSN-BDNF), to verify the characteristics of the microbubbles, and to study the therapeutic effect of the microbubbles combined with ultrasound on the opening of the blood–brain bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Therefore, we should interpret this result cautiously. Indeed, learning deficits are often associated with a reduction in synaptophysin expression by 25% to 40% in the hippocampus (Cinar et al, 2020; Veschsanit et al, 2021; Wang et al, 2021), which is, at least, the double of the reduction we found. Moreover, at that time point, there is a lack of synaptic long‐term depression (LTD) in the hippocampus of alcohol‐treated rats and a decrease in learning (Drissi et al, 2020; Silvestre de Ferron et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, we should interpret this result cautiously. Indeed, learning deficits are often associated with a reduction in synaptophysin expression by 25% to 40% in the hippocampus (Cinar et al, 2020; Veschsanit et al, 2021; Wang et al, 2021), which is, at least, the double of the reduction we found. Moreover, at that time point, there is a lack of synaptic long‐term depression (LTD) in the hippocampus of alcohol‐treated rats and a decrease in learning (Drissi et al, 2020; Silvestre de Ferron et al, 2015).…”
Section: Discussionsupporting
confidence: 56%
“…Regulation that protects neuronal survival is essential in the pathological process of alleviating neurological complications caused by neuroinflammation [ 2 , 31 ]. In the development of neuronal, BDNF, as an important nerve growth factors, plays an important role in the growth, survival, and differentiation of neurons [ 32 ]. BDNF enhances neuronal survival and protects synaptic function by binding to tropomyosin receptor kinase B (TrkB) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2-Distearoyl-sn-Glycero-3-EthylPhosphocholine (DSEPC) (Avanti Polar Lipids, Alabama, USA), which was dissolved in chloroform and added to the DBPC and PEG40s mixture, at a molar ratio of DBPC: PEG40s:DSEPC of 9:0.5:1 as reported previously in similar formulations ( Delalande et al., 2017 ; Wang et al., 2021 ). All MB formulations were applied to biofilms immediately after production.…”
Section: Methodsmentioning
confidence: 99%